2020
DOI: 10.3390/cancers12113282
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Lobectomy for Low to Intermediate Risk Differentiated Thyroid Cancer

Abstract: Many recent publications and guidelines have promoted a “more is less” approach in terms of treatment for low to intermediate risk differentiated thyroid cancer (DTC), which comprise the vast majority of thyroid cancers: less extensive surgery, less radioactive iodine, less or no thyroid hormone suppression, and less frequent or stringent follow-up. Following this approach, thyroid lobectomy has been proposed as a means of decreasing short- and long-term postoperative morbidity while maintaining an excellent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…The presence of suspicion of ETE represents an indication for surgery rather than for active surveillance, however (24,25). Hemithyroidectomy is considered as an effective treatment with lower rates of surgical complications for low risk DTC patients (26,27). Neck US plays a pivotal role in the preoperative workup for the selection of potential candidates for hemithyroidectomy as opposed to those who may benefit from more extensive initial surgery (28).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of suspicion of ETE represents an indication for surgery rather than for active surveillance, however (24,25). Hemithyroidectomy is considered as an effective treatment with lower rates of surgical complications for low risk DTC patients (26,27). Neck US plays a pivotal role in the preoperative workup for the selection of potential candidates for hemithyroidectomy as opposed to those who may benefit from more extensive initial surgery (28).…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that the operative extent of patients with unilateral multifocal PTC was not associated with risk of recurrence. Various guidelines and recent publications have promoted a “less is more” approach for the treatment of low-risk PTC, which represents the vast majority of thyroid cancers; this involves less extensive operation, less radioiodine, and less or no thyroid hormone suppression [ 23 ]. A global trend toward less radical surgical procedures, including thyroid lobectomy, has also gained traction in recent years [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the clinical guideline recommendations were revised in order to avoid over-diagnosis in patients with low-risk thyroid nodules, aiming to promptly identifying patients with advanced or high-risk tumors requiring aggressive treatment approaches [16]. This involved discouraging screening programs [17,18], biopsy of suspicious subcentimeter nodules [10], and favoring less extensive surgery [19,20] and radioiodine use [21], as well as reducing the burden of post-surgical follow-up examinations [22,23]. These efforts are consistent with the general trend in reducing low-value care [24].…”
Section: Discussionmentioning
confidence: 99%